Policy framework for information systems strategic plan Municipality of Del Carmen - Coro, Alfredo Matugas II (University of the Philippines Diliman, 2011)
The national government through the Commission on Information and Communications Technology relentlessly requested each local government to develop and submit an Information Systems Strategic Plan (ISSP). The ISSP was viewed to present the overall strategic plan of a local government unit for the development, implementation and utilization of information communications technology (ICT). Previous reviewed processes and literature did not directly define to alignment of the objective of the local government with the ICT plan. The project was to develop a policy framework for developing the ISSP for the Municipality of Del Carmen that will address a specific development objective of the local government including an initial implementation. The primary objective of the ISSP is to increase the competitiveness of the municipality in getting investors through good governance powered by ICT. In the process of the project implementation with the local government, it was learned that two separate yet interrelated processes and execution strategies to ensure the quality of the output of the document : (1) The development of the policy framework which deals with the objective of this study and the expected outputs; (2) The development of the project which deals with making the political ties and negotiations to ensure the support of the local government in the execution of the project. The output of the project includes the endorsement for the Legislative Body to adopt The Del Carmen Investment Priority Plan, The ISSP Policy Framework and The Updated ISSP of Del Carmen. The initial implementation immediately had positive results through new queries for business and continuation of the existing investors in Del Carmen. The ISSP policy framework allowed the local government and the community to have better understanding of the utilization of information and communications technology to achieve the goal of the municipality.